Sexual selection and the differential effect of polyandry. - Collet, J; Richardson, D; Worley, K; Pizzari, T (2012)
In principle, widespread polyandry (female promiscuity) creates potential for sexual selection in males both before and after copulation. However, the way polyandry affects pre- and postcopulatory episodes of sexual selection remains little understood. Resolving this fundamental question has been difficult because it requires extensive information on mating behavior as well as paternity for the whole male population. Here we show that in replicate seminatural groups of red junglefowl, Gallus gallus, polyandry eroded variance in male mating success, which simultaneously weakened the overall intensity of sexual selection but increased the relative strength of postcopulatory episodes. We further illustrate the differential effect of polyandry on pre- and postcopulatory sexual selection by considering the case of male social status, a key determinant of male reproductive success in this species. In low-polyandry groups, however, status was strongly sexually selected before copulation because dominants mated with more females. In high-polyandry groups, sexual selection for status was weakened and largely restricted after copulation because dominants defended paternity by mating repeatedly with the same female. These results reveal polyandry as a potent and dynamic modulator of sexual selection episodes.